Exploring the Impact of Health Insurance on Health Care Utilization and Outcome Using Electronic Medical Record Data - Yuan Xu; Mingshan Lu; Ning Li; Elijah Dixon; Robert Myers; Hude Quan (International Journal of Population Data Science, 2017)
ABSTRACT